Prevention of oxytosis-induced c-Raf down-regulation by (arylthio)cyclopentenone prostaglandins is neuroprotective. (1st September 2017) - Shibata, Shoko; Furuta, Kyoji; Oh-hashi, Kentaro; Ueda, Hiroshi; Kiuchi, Kazutoshi; Hirata, Yoko
Highlights: Down-regulation of c-Raf contributed to glutamate-induced oxytosis. Neuroprotective (arylthio)cyclopentenone prostaglandins preferentially bound to c-Raf. (Arylthio)cyclopentenone prostaglandins prevented down-regulation of c-Raf, resulting in neuroprotection against oxidative stress. Abstract: Prolonged exposure to high concentrations of glutamate leads to cell type specific glutathione depletion and resulting oxidative stress, known as oxytosis. As a result of glutathione depletion, accumulation of reactive oxygen species and Ca 2+ influx are increased; however, the specific target of oxytosis has yet to be identified. In the present study, we focused on the effect of glutamate-induced oxidative stress on the extracellular-regulated protein kinase (ERK) pathway using the murine hippocampal HT22 cell line. Although the contribution of the ERK pathway to glutamate-induced oxytosis in HT22 cells is controversial, Western blot analysis revealed that glutamate caused down-regulation of mitogen-activated protein kinase kinase kinase (c-Raf) and a resulting decrease in the phosphorylation of c-Raf, as well as of mitogen-activated protein kinase kinase1/2 (MEK1/2) and ERK1/2, downstream components of the c-Raf/MEK/ERK pathway. Furthermore, neuroprotective (arylthio)cyclopentenone prostaglandins prevented glutamate-induced c-Raf down-regulation and consequently maintained the basal activity of c-Raf and its downstream signaling components. A pull-down assay using biotin-labeled cyclopentenone prostaglandins revealed that they preferentially bound to c-Raf relative to other signaling molecules of the ERK pathway, including Ras, MEK1/2, and ERK. These results suggest that neuroprotective (arylthio)cyclopentenone prostaglandins directly bind to c-Raf protein and protect cells from down-regulation of the c-Raf protein itself, resulting in neuroprotection against oxidative stress.